Study of the Properties of Bearberry Leaf Extract as a Natural Antioxidant in Model Foods - Nurul Aini, Mohd Azman; Gallego, Maria Gabriela; Segovia, Francisco; Sureena, Abdullah; Shalyda, Md Shaarani; Pablos, Maria Pillar Almajano (MDPI AG, 2016)
The common bearberry (Arctostaphylos uva-ursi L. Sprengel) is a ubiquitous procumbent evergreen shrub located throughout North America, Asia, and Europe. The fruits are almost tasteless but the plant contains a high concentration of active ingredients. The antioxidant activity of bearberry leaf extract in the 2,21-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation assay was 90.42 mmol Trolox equivalents/g dry weight (DW). The scavenging ability of the methanol extract of bearberry leaves against methoxy radicals generated in the Fenton reaction was measured via electron paramagnetic resonance. Lipid oxidation was retarded in an oil–water emulsion by adding 1 g/kg lyophilised bearberry leaf extract. Also, 1 g/kg of lyophilised bearberry leaf extract incorporated into a gelatin-based film displayed high antioxidant activity to retard the degradation of lipids in muscle foods. The present results indicate the potential of bearberry leaf extract for use as a natural food antioxidant.